Development of an innovative, ecological and stability-indicating analytical method for semiquantitative analysis of ampicillin sodium for injection by thin layer chromatography (TLC) - Tótoli, Eliane Gandolpho [UNESP]; Salgado, Hérida Regina Nunes [UNESP] (My University, 2014)
Ampicillin sodium is a β-lactam antimicrobial agent for parenteral use, widely used in many parts of the world and recommended by the World Health Organization. There are some methods described in the literature to identify ampicillin sodium employing Thin-Layer Chromatography (TLC). However, these methods are complex and require the use of solvents potentially toxic to the operators and environment. This paper describes the validation of an innovative semiquantitative method for the analysis of ampicillin sodium in powder for injectable solution, using TLC. This technique does not use toxic or expensive solvents, which is one great advantage over the described TLC analytical methods. This fact contributes to minimize the generation of toxic organic solvent waste by the industry and thereby reduces the impact of its activities on the environment. The method involved the use of a mobile phase comprised by a mixture of ethanol and water (90:10, v/v) and the stationary phase was silica gel impregnated in aluminum. Stress degradation studies of the pharmaceutical product were conducted under conditions of hydrolysis (acid, basic, and aqueous), oxidation and photolysis. The spots were detected by exposing the dry plate to UV chamber (254 nm) and/or iodine vapor and analyzed semiquantitatively by HPLC-UV. The method was successfully validated according to the ICH guidelines and Brazilian legislation, showing to be able to semiquantify ampicillin sodium in powder for injection preparation and it can be used as an environmentally friendly alternative for the routine analysis in quality control.
Keywords: Ampicillin sodium; Analytical methods; Quality control; TLC; Stability